Ocular Involvement in Coronavirus Disease 2019: Up-to-Date Information on Its Manifestation, Testing, Transmission, and Prevention - Chen, Ziyan; Yuan, Gang; Duan, Fang; Wu, Kaili (Frontiers in Medicine, 2020)
The coronavirus disease 2019 (COVID-19) pandemic, caused by the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is still underway. An understanding of the virus’s mode of transmission and infection is required for its effective containment. Besides the respiratory and digestive tracts, the ocular surface presents an additional mucosal surface that is exposed to infectious droplets and direct/indirect contact. The relationship between SARS-CoV-2 infection and the eye remains controversial. This review examines up-to-date information on ocular manifestation, laboratory testing, transmission, and prevention of COVID-19. Based on clinical observations, the risk of conjunctivitis in COVID-19 is low. Despite the low incidence, positive SARS-CoV-2 results in eye specimens suggest that the ocular surface may harbor SARS-CoV-2, which may increase the infection and transmission risk. We conclude that the ocular surface remains a potential transmission route for the virus that should not be ignored. In addition, the intraocular findings have also been described in COVID-19. The measures for eye and face protection should be widely adopted to stem the tide of the pandemic.